Lord Plender: Some Writings and Speeches / Random Reminiscences / Case Lore or Leaves from the Notebook of a Professional Accountant (Book). - Cannon, Arthur M.; Murphy, Mary E. (The Accounting Review, 1952)
Reviews three books on accounting. "Lord Plender: Some Writings and Speeches," edited by Lady Plender; "Random Reminiscences," by Arthur Cutforth; "Case Lore or Leaves From the Notebook of a Professional Accountant," by Ernest Evan Spicer.